Assistance of Android-Based Diabetes Mellitus Risk Early Detection Model Application - Syahid, Syahid Amrullah; Pratama, Kharisma; pradika, Jaka; Kim Jiu, Cau; Wuriani, Wuriani; Usman, Usman (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
DM cases in the world are still very high, where an increase is reported, in 2019 there were 463 million to 537 million people in 2021. Several cases of DM patients and even those who have experienced complications of diabetic foot ulcers have been found based on reports from the Sungai Ambangah village. This should be a concern, not only taking action on patients who have experienced complications, because preventive measures must also be a priority to be carried out, so that no more people experience DM. Therefore, to increase awareness of the importance of improving lifestyle in order to avoid DM disease, early detection is needed. One of them can be by utilizing an android application (Si Manis)